REPRESENTATION OF IMAGES WITH IMITATIVE WORDS IN THE NOVEL “THE LEGEND OF MAMAN BIY” BY T.QAYIPBERGENOV - Bayımbetova, M.B.; Mambetniyazova, H.M. (SCIENCE and SOCIETY, 2025)
The article discusses the thoughts and feelings of the characters in T.Qayipbergenov’s work "The Legend of Maman Biy", their attitudes toward surrounding events, as well as how the use of imitative words in descriptions of inanimate nature lends a sense of artistry to the literary language, as illustrated by examples.